A Systematic Review: Impact of Caesarean Rate after Implementation of Robson’s Criteria at Secondary and Tertiary Hospital - Octavianty, P (KnE Life Sciences, 2018)
When medically justified, a caesarean section can effectively prevent maternal and perinatal mortality and morbidity. However, there is no evidence showing the benefits of caesarean delivery for women or infants who do not require the procedure [1]. In recent years, governments and clinicians have expressed concern about the rise in the numbers of caesarean section births and the potential negative consequences for maternal and infant health [1–4]. This study aims to provide a description of how Robson’s criteria give an implication of decreasing caesarean rate. This is a literature study, online databases such as ProQuest, JSTOR, EBSCO, Biomedicina were searched with time restriction from 2000 to 2016. The population of this study were taken from five countries with different culture, demography, per capita income and public health policy such as Canada, Ireland, Singapore, Peru, Lithuania, and India. Of the five countries, only Canada has a decreasing caesarean rate Intervention groups of lowrisk pregnancy change 22.5% to 21.8% (CI 0,80 to 0,99 adjusted risk difference –1.8% (95% CI –3.8 to 0.2) but Intervention groups of high-risk pregnancy change 23.3% to 23.5% with p = 0.35; p 0.03 for interaction. Other countries still have an increasing caesarean rate. The implementation of Robson’s criteria should be customized with the ability in healthcare providers and also health policy in each country. Keywords: impact, caesarean rate, Robson’s, hospital